ANALISIS PENGGUNAAN CLOUD COMPUTING TERHADAP EFEKTIVITAS PENGENDALIAN INTERNAL DALAM PROSES AUDIT INTERNAL - Gunawan, Zahra; Fahriani, Dian (JURNAL AKUNTANSI BARELANG, 2025)
This study aims to provide readers with an understanding of the application of cloud computing to effectiveness in the audit process, the use of cloud computing in internal control and the use of cloud computing in the audit process. The research method used qualitative methods obtained from interviews with informants. The results showed that cloud computing is a tool used in the internal quality audit process which is used as a centralized data storage for audits and can be accessed through a dashboard. It provides convenience in document access and speeds up audit documents. However, cloud computing has obstacles in data security in the risk of data leakage. In overcoming this, there is a separation of duties in granting cloud computing access approval.